Putting Business Students in the Shoes of an Executive: An Applied Learning Approach to Developing Decision Making Skills - Jeanny Liu; Deborah Olson (Park University, 2011)
Students often struggle with how to translate textbook concepts into real-world applications that allow them to personally experience the importance of these concepts. This is an ongoing challenge within all disciplines in higher education. To address this, faculty design their courses using methods beyond traditional classroom lectures to facilitate and reinforce student learning. The authors believe that students who are given hands-on problem-solving opportunities are more likely to retain such knowledge and apply it outside the classroom, in the workplace, volunteer activities, and other personal pursuits. In an attempt to engage students and provide them with meaningful opportunities to apply course concepts, the authors have initiated a number of experiential learning methods in the classroom. Since fall of 2008, elements of problem-based learning were integrated in the authors' business courses. Specifically, real-world consulting projects were introduced into their classrooms. This paper focuses on the authors' experiences implementing problem-based learning processes and practical project assignments that actively engage students in the learning process. The experiences and the feedback gathered from students and executives who participated in the "realworld" project are reported in this paper.